Mediating role of Environmental Education for Sustainable Supply chain Performance: Empirical Evidence from Chemical Companies of Pakistan - Ikramuddin Junejo; Fiza Qureshi; Muhammad Ali Khan (Faculty of Economic and Business, 2023)
Previous studies have been conducted in developed countries, and only a few are conducted in developing countries. Furthermore, a contribution of this is that the mediating role of environmental education is considered in the present study. This study aimed to identify the mediating role of environmental education between internal environmental management, supplier selection, and green packaging on sustainable supply chain performance in Pakistan. A total of 250 chemical companies filled out the questionnaire. The findings of this study revealed a partial mediation effect of environmental education for internal environmental management, supplier selection, and green packaging in sustainable supply chain performance in Pakistan. However, the supplier selection results are more critical compared to internal environment management and green packaging due to the higher beta value. This study proposed a pivotal variable to achieve a sustainable supply chain in developing countries such as Pakistan.JEL Classification: Q01, Q51, Q54, Q56How to Cite:Junejo, I., Qureshi, F., & Khan, M. A. (2023). Mediating role of Environmental Education for Sustainable Supply Chain Performance: Empirical Evidence from Chemical Companies of Pakistan. Etikonomi, 22(1), 131–142. https://doi.org/10.15408/etk.v22i1.27139.